Intimate Partner Violence and Custody Decisions: A Randomized Controlled Trial of Outcomes from Family Court, Shuttle Mediation, or Videoconferencing Mediation, Washington D.C., 2017-2018 - Holtzworth-Munroe, Amy ([Verlag nicht ermittelbar], 2021)
Among divorcing and separating parents referred by family courts to mediation to resolve issues, over half report intimate partner violence (IPV). Whether family mediation can be safely offered to cases with a history of IPV is a major controversy that has not been examined previously with empirically sound research. This study was a randomized controlled trial, the "gold standard" for assessing interventions, of family mediation cases with levels of IPV that would, historically, be considered inappropriate for mediation at our study site, a court-attached mediation center in Washington, D.C. Study cases were randomly assigned to one of three study conditions: traditional court-based litigation (n=67), shuttle mediation (n=49), or videoconferencing mediation (n=50). Researchers conducted a randomized control trial to compare immediate and one year outcomes for three dispute resolution processes (i.e., traditional court-based litigation, shuttle mediation, and videoconferencing mediation) among family law cases seeking to resolve parenting related issues and self-reporting a level of IPV history that would typically prohibit joint mediation as an option at the court-annexed mediation program where the study was conducted. The mediation intake interview included an IPV screening measure, the Mediator's Assessment of Safety Issues and Concerns (MASIC; Holtzworth-Munroe, Beck, and Applegate, 2010). There is initial evidence of the reliability and validity of the MASIC (Pokman et al., 2014) and research demonstrating that the MASIC leads to higher levels of detection of IPV among parents seeking mediation than other methods of IPV screening (Rossi, et al., 2015). The MASIC is a behaviorally specific measure, listing a series of abusive behaviors on subscales (e.g., psychological abuse, coercive control, physical violence, sexual violence, stalking) and consequences of abuse (e.g., fear of the partner, injury). Each item is assessed for occurrence twice-- ever in the relationship and in the past year. The questions ask the party about their victimization from the other party. Based on party responses to the Multi-Door intake interview, including the MASIC, the DRSs identified cases as being potentially eligible for the study if the level of IPV reported by either or both parties was at a level that the case was considered inappropriate for joint mediation. No specific level of IPV for study eligibility was set, for two reasons. First, no previous empirical data are available to guide decisions regarding what level of IPV would make joint mediation inappropriate. Second, the DRSs were well trained and experienced and wanted to retain the right to use their clinical judgment. However, the Multi-Door staff and research team agreed that DRSs would pay particular attention to level and types of IPV, presence of risk factors empirically related to lethality (e.g., weapons), whether IPV was escalating in frequency or severity, IPV-related injuries, and whether a party was fearful of the other party or expressed IPV-related concerns about participating in mediation.